The Mammoth book of eyewitness ancient Egypt - Lewis, Jon E. 1961-. (New York Carroll & Graf Publishers, 2003)
Walk with the pharaohs through the ancient land watered by the Nile.
"From Pharaohs to peasants, pyramid building to working on the Nil delta, over 100 eyewitness documents revealing Ancient Egyptian history and day-to-day life from 3150BC to 30BC"--Cover.
Keywords: Egypt -- Civilization; Egypt -- History; Egypt -- Antiquities